2022
DOI: 10.1021/jacs.1c12538
|View full text |Cite
|
Sign up to set email alerts
|

Colloidal-ALD-Grown Hybrid Shells Nucleate via a Ligand–Precursor Complex

Abstract: Colloidal atomic layer deposition (c-ALD) enables the growth of hybrid organic–inorganic oxide shells with tunable thickness at the nanometer scale around ligand-functionalized inorganic nanoparticles (NPs). This recently developed method has demonstrated improved stability of NPs and of their dispersions, a key requirement for their application. Nevertheless, the mechanism by which the inorganic shells form is still unknown, as is the nature of multiple complex interfaces between the NPs, the organic ligands … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(26 citation statements)
references
References 89 publications
2
24
0
Order By: Relevance
“…This growth procedure for a thicker shell could be further optimized by adding extra ligands as previously demonstrated with AlMe3 on a wide range of NC systems. 28,29 Bulk structural and optical characterization. Growth of metal oxide shells is indicated by transmission electron microscopy (TEM).…”
Section: Growth Of Metal Oxide Shells On Inp Qdmentioning
confidence: 99%
See 1 more Smart Citation
“…This growth procedure for a thicker shell could be further optimized by adding extra ligands as previously demonstrated with AlMe3 on a wide range of NC systems. 28,29 Bulk structural and optical characterization. Growth of metal oxide shells is indicated by transmission electron microscopy (TEM).…”
Section: Growth Of Metal Oxide Shells On Inp Qdmentioning
confidence: 99%
“…In light of the need for atomically precise control over surface structure and stoichiometry, there has been growing interest in the field to explore layer-by-layer growth of heterostructures. 5,[26][27][28][29] Talapin et al have demonstrated the synthesis of "digital" nano-heterostructures through colloidal atomic layer deposition (c-ALD), inspired by the conventional method of solid film deposition. 26,27 While conventional ALD leverages repeated cycles of alternating self-limiting reactions in the vapor phase, c-ALD relies on the phase change of nanomaterials in liquids and requires preservation of colloidal stability between transfer steps.…”
Section: Introductionmentioning
confidence: 99%
“…43,44 Further, work by Segura Lecina et al demonstrated that c-ALD of alumina is governed via ligand−precursor interactions, which result in a hybrid organic/inorganic shell. 45 These observations suggest that introducing ligands that interact with the c-ALD precursor could promote their efficient incorporation within the hybrid oxide shell. This strategy would increase the ligand coverage without requiring a ligand exchange process.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Herein, we propose the synthesis of a hybrid organic/inorganic shell as a strategy to efficiently immobilize organic chromophores in close proximity of the NC surface and with tunable density. Recently, the development of colloidal atomic layer deposition (c-ALD) of metal oxides, such as amorphous alumina, was demonstrated to tightly anchor the otherwise dynamic ligands to the NC surface and, thus, to confer the inorganic NC core enhanced stability. , Further, work by Segura Lecina et al demonstrated that c-ALD of alumina is governed via ligand–precursor interactions, which result in a hybrid organic/inorganic shell . These observations suggest that introducing ligands that interact with the c-ALD precursor could promote their efficient incorporation within the hybrid oxide shell.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to expanding dimensionality, each cALD cycle requires precise control over reaction sequence, relative concentrations, and reaction time, as many reaction pathways can happen in parallel depending on these parameters. For example, it was recently shown that beyond colloidal stabilization, oleate ligands are necessary for metal oxide nucleation and growth via single-phase cALD approaches 19 . Such steps can also be nondeterministic.…”
mentioning
confidence: 99%